2006
DOI: 10.1089/bfm.2006.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a User-Friendly Centrifuge for Measuring Creamatocrits on Mothers' Milk in the Clinical Setting

Abstract: The creamatocrit (CRCT), a simple, accurate, and inexpensive technique for the estimation of lipid and caloric content in mothers' milk, has been used extensively in lactation research, but has not been integrated into the routine management of clinical lactation problems such as slow weight gain in mothers' milk-fed preterm and term infants. The Creamatocrit Plus is a lightweight, noiseless centrifuge with an embedded reader that automatically calculates lipid and calories from the CRCT value, making it ideal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 37 publications
1
45
0
2
Order By: Relevance
“…Although a useful bedside, cheap estimate of human milk fat and caloric content, creamatocrit is less accurate and even tends to overestimate human milk fat as compared with biochemical methods or midinfrared technology. 18,19 Finally, the method of milk expression is not described in the study by Fujimori et al, 10 and it is unclear to us how these authors were technically able to obtain 10 ml of colostrum in all participants; indeed as colostrum production consists of only a few milliliters during the first few days of life, 20 we speculate that the 10 ml collection was a cumulative collection over the few days in the study by Fujimori et al 10 In our study, maternal BMI appeared not to significantly correlate with most macronutrient and energy content of human colostrums, with the exception of protein concentration. The positive correlation between protein concentration in colostrum and maternal BMI requires a few comments: first, its mechanism is unclear, and among other possibilities, it would be important to determine whether differences in maternal diet might be influential.…”
Section: Discussionmentioning
confidence: 99%
“…Although a useful bedside, cheap estimate of human milk fat and caloric content, creamatocrit is less accurate and even tends to overestimate human milk fat as compared with biochemical methods or midinfrared technology. 18,19 Finally, the method of milk expression is not described in the study by Fujimori et al, 10 and it is unclear to us how these authors were technically able to obtain 10 ml of colostrum in all participants; indeed as colostrum production consists of only a few milliliters during the first few days of life, 20 we speculate that the 10 ml collection was a cumulative collection over the few days in the study by Fujimori et al 10 In our study, maternal BMI appeared not to significantly correlate with most macronutrient and energy content of human colostrums, with the exception of protein concentration. The positive correlation between protein concentration in colostrum and maternal BMI requires a few comments: first, its mechanism is unclear, and among other possibilities, it would be important to determine whether differences in maternal diet might be influential.…”
Section: Discussionmentioning
confidence: 99%
“…Meier et al 20 used a creamatocrit device and showed it is an accurate way to measure fat (r 2 ¼ 0.90). Creamatocrit, however, does not measure carbohydrate or protein.…”
Section: Discussionmentioning
confidence: 99%
“…Currently available methods for measuring human milk content include the creamatocrit, ultrasonic analyzers, midinfrared spectrophotometers and near-infrared (NIR) spectrophotometry. [19][20][21] NIR spectrophotometry is a promising method for providing point-of-care measurements of human milk macronutrients with several distinct advantages over other technologies. NIR spectrophotometry uses the wavelength spectrum 1200 to 2400 nm to analyze material of solid and liquid states.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the improved efficacy of SIM expression resulted in milk that had a higher cream content compared with SEQ expression (Table 2). Given the close relationship between the cream content and the energy content of milk, 14 the milk yielded by SIM will have a higher energy content than that yielded by SEQ.…”
Section: Discussionmentioning
confidence: 99%
“…12 During this period, mothers hand-expressed small milk samples (< 1 mL) into 5-mL polypropylene vials (Disposable Products, Adelaide, Australia), immediately before and after each breastfeed or expression. The breastfeed volumes and cream contents of the milk samples (measured by the creamatocrit method 13 on the Creamatocrit PlusÔ device 14 [Medela Inc., McHenry, IL]) were used to calculate the breastfeeding storage capacity as described previously. 15 Before and after each pumping session the mothers hand-expressed small milk samples (< 1 mL) from the breast being expressed.…”
Section: Measurement Of 24-hour Milk Production and Calculation Of Stmentioning
confidence: 99%